Depth Match: Performance, History, and Digital Games. - Leichman, Jeffrey M. (Eighteenth Century: Theory & Interpretation)
The article focuses on ongoing project of developing a video game based on the marginal theaters that flourished at seasonal fairs in early eighteenth-century Paris, France. It mentions how the VESPACE digital model distributes interpretation of sources across textual, spatial, and algorithmic representations. It also mentions effects of gamification on writing cultural history, in service of a sustainable digital humanities practice that recognizes the necessary interdependence.